Accelerating Methane Reductions in Rice Production Systems through Market-based Mechanisms: Results of Farmer Surveys and Choice Experiments in the Philippines - Villanueva, Donald B.; Pajadan, Karen M.; Cabrera, Ellanie R.; Malana, Xyla Mae L.; Revicoy, Riela Rose R.; Mirzabaev, Alisher (International Rice Research Institute, 2025)
Rice cultivation significantly contributes to methane emissions and consumes substantial amounts of water, making it a key area for agricultural climate mitigation. Recognizing this, the Philippine Government has prioritized the widespread adoption of Alternate Wetting and Drying (AWD) technology across 3.21 million hectares of irrigated rice fields, with the goal of reducing greenhouse gas emissions by approximately 62.8 million metric tons of carbon dioxide equivalent (mmtCO₂e). Nevertheless, actual field-level adoption of AWD and other low-emission rice (LER) practices remains limited.